Dual-power water pump and water source heat pump system - TONG XIANWEN; XU HONGYAN; XIE MENG; TONG YILUN (2018)
The invention discloses a dual-power water pump which comprises an engine, a power generator, a water pump motor and a water pump body. The invention further discloses a water source heat pump system.The water source heat pump system comprises one or more water pump and a heat pump unit. At least one of the water pumps is the dual-power water pump. The dual-power water pump and the water source heat pump system have the advantages that the dual-power water pump can be driven by the engine and the motor, and power further can be generated by the dual-power water pump; electric power and natural gas can be adopted for the dual-power water pump and the water source heat pump system, and accordingly merits of the electric power and merits of the natural gas can complement one another; the dual-power water pump and the water source heat pump system can be in diversified running modes and have obvious economic benefits and social benefits. 本发明公开了种双动力水泵，包括发动机、发电机、水泵电机和水泵泵体，其中水泵可以采用发动机、电机驱动，还能发电；还公开种水源热泵系统，包含台或台以上水泵和